Implementasi Pendidikan Karakter Dalam Pembelajaran IPS Materi Sejarah Di SMP Negeri 2 Timang Gajah - Selviana, Anita; Nugraha, Muhammad Adika; Nababan, Surya Aymanda (Toga Jurnal Keguruan dan Ilmu Pendidikan, 2024)
This study aims to examine the implementation of character education in learning Social Sciences (IPS), especially on historical material at SMP Negeri 2 Timang Gajah. Character education is an important part of education that serves to form students who have a positive attitude, responsibility, and good social ethics. The implementation of character education in learning (social studies), especially in history material, is one way to instill character values in students through learning history, by learning history students can apply and model the values contained in historical events. This research uses a descriptive qualitative approach. with observation, interview, and documentation methods to collect data. The results obtained from this study show that teachers succeeded in integrating moral values such as honesty, responsibility, and tolerance through interactive teaching methods and analysis of historical figures. This approach not only improves students' understanding of historical material, but also encourages the application of character values in everyday life. The implementation of character education in learning social studies history material is effective in shaping students' positive behavior in accordance with the moral values taught.